Single neutral pion production by charged-current ν-μ interactions on hydrocarbon at 〈Eν〉=3.6 GeV - Le T. (2015)
Single neutral pion production via muon antineutrino charged-current interactions in plastic scintillator (CH) is studied using the MINERvA detector exposed to the NuMI low-energy, wideband antineutrino beam at Fermilab. Measurement of this process constrains models of neutral pion production in nuclei, which is important because the neutral-current analog is a background for appearance oscillation experiments. The differential cross sections for momentum and production angle, for events with a single observed and no charged pions, are presented and compared to model predictions. These results comprise the first measurement of the kinematics for this process.